1901 Ariz. Acts 1251, Crimes Against the Public Peace, § 381 - (:unkn) unknown (General Publisher, 1901)
Prohibited discharge of a gun, pistol, or other firearm in any saloon, dance house, store or other public ouse or business house in the territory. Also prohibitd injury, destruction, or damage of property therein. Violators fined not exceeding three hundred dollars or imrpsioned in jail not exceeding six months, or both.
--
Keywords: DISCHARGE